Analisis Dampak Restoran Richeese Terhadap Kinerja Jalan Bau Massepe - suwardi suwardi; Rahmawati Rahmawati; Imam Fadly; misbahuddin misbahuddin; Jabir Muhammadiyah (Journal of Innovative and Creativity, 2026)
The Richeese restaurant on Bau Massepe Road in Parepare City has the potential to cause a significant negative impact on traffic performance on this road, which has previously experienced congestion problems, especially during rush hour. This study aims to analyze and identify the extent of the traffic impact caused by the restaurant's operations, as well as the dominant factors causing congestion in the area around the location. The methods used are quantitative and qualitative approaches involving direct observation surveys in the field. Data collection includes geometric road surveys, vehicle traffic volume, speed, and side obstacles. Peak traffic data was identified on weekdays (Monday) with a volume of 696.1 smp/hour and on holidays (Sunday) with a volume of 485.6 smp/hour. Road and intersection performance analysis used the 2023 Indonesian Road Capacity Guidelines (PKJI) to calculate key parameters such as Capacity (C), Degree of Saturation (DJ), and Level of Service (LOS). The analysis results show that the presence of Richeese Restaurant, particularly parking activities on the road shoulder and high vehicle entry/exit movements, are the main factors causing side obstacles that interfere with the effectiveness of road operation. This impact causes an increase in the Degree of Congestion and a decrease in the Level of Service (LOS) during peak hours, indicating traffic flow disruption. Therefore, this study recommends the need for traffic management measures and road facility improvements to manage and mitigate the negative impacts caused.